Propriedades psicométricas de um instrumento para avaliar o envolvimento de idosos em atividades prazerosas - Ferreira, Heloísa Gonçalves (Universidade Federal de São Carlos, 2015)
Researchers have identified various factors that affect seniors’ well-being, including their engagement with life. As such, to help seniors with mental health problems, one strategy is to increase the frequency of their involvement in pleasant events. However, there are no instruments that Brazilian professionals can use, to identify activities that are pleasant for a specific older person. Thus, the aim of this doctoral research program was to investigate the psychometric properties of an instrument culturally adapted for use in Brazil, the COPPES-BR, which can be used to assess older people’s engagement in pleasant events. First, a literature review was conducted to describe the context in which the original instrument (the California Older Person’s Pleasant Events Schedule - COPPES) was developed, its theoretical underpinnings, and to define the construct this instrument measures. Next, in Manuscript 1, initial evidence of the validity of the COPPES-BR is presented. In total, 337 Brazilian, community-dwelling seniors (68,2% female), without cognitive impairments, between the ages of 60 and 93 (M = 69.7; sd = 7.31), living in neighborhoods with different levels of social vulnerability, responded to the following instruments, all adapted for use in Brazil: (a) the COPPES-BR, (b) the Beck Depression Inventory (BDI), (c) the Pfeffer Index, to evaluate functional dependency, and (d) sociodemographic questions. The internal consistency of the Frequency, Pleasure, and Obtained Pleasure scales was excellent (Cronbach’s alpha values of .96, .95 and .97, respectively). In addition, Frequency and Obtained Pleasure scores were negatively correlated with depressive symptoms. Thus, initial evidence of precision and external validity were found. However, the results of a confirmatory factor analysis, to compare the responses of American and Brazilian participants, indicate that the dimensions established for the original instrument do not explain the responses obtained with Brazilians. Thus, in Manuscript 2, the results of an exploratory factor analysis are presented, suggesting that Brazilians respond to the COPPES-BR on the basis of four domains: F1 – Social Activities and Competence (α = .94); F2 - Contemplative Activities (α = .83); F3 - Practical Activities (α = .72); and F4 - Intellectual Activities (α = .70). The factor solution explained 43.6% of the total variance. In Manuscript 3, additional evidence of the external validity of the COPPESBR is presented, examining relationships between respondents’ scores on the four factors of the Frequency scale and: (a) sociodemographic indicators, (b) functional dependence, and (c) depressive symptoms. The factor scores were negatively correlated with depressive symptoms and functional dependence scores, and positively correlated with purchasing power and educational level. The correlations with depressive symptoms add to the evidence of the external validity of the COPPES-BR. The other results suggest that the frequency of seniors’ involvement in pleasant events is also affected by functionality and sociodemographic factors. Thus, although there is already satisfactory evidence of the internal and external validity of the COPPES-BR, additional studies are needed, using more representative samples of Brazilian older people, to strengthen the evidence regarding the precision and validity of this instrument.
Keywords: pleasurable activities; validity; scale; elderly; Atividades prazerosas; validade; escala; idosos; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO